Diagnostic, Prognostic and Predictive Biological Markers in Bladder Cancer - Illumination of a Vision 2.0 - Ecke, Thorsten; Otto, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
After our successful first Special Issue about bladder cancer, we proceeded with the second issue. Again, many international scientists submitted their newest research results in that extremely interesting field and followed our call for submissions. It is not only the collection and combination of old and new markers that could develop new possibilities, but also the focus on different classifications and sub-classifications that will unveil new ways in diagnostic and therapeutic approaches. It seems that the two established diagnostic tools will still play an important role, but new markers and diagnostics tools will present more detailed and more differentiated possibilities in the treatment of urinary bladder cancer. This second Special Issue is full of scientific results that could provide new ways to help patients with instruments for early diagnostics and with predictive and prognostic markers on their way to finding new and personalized strategies for therapy. The editors thank all of the submitting authors for their efforts and time spent on each manuscript. We hope that this Special Issue will prove useful to research work in bladder cancer in the future. We hope that many talented researchers will use multiple forms of art to improve their professional successes and to ameliorate diagnostics and therapy in bladder cancer.